Identification of 3 novel HLA‐B alleles: B*08:173, B*18:72:03 and B*53:05:02. (29th December 2016) - Brunet, L.; Bettens, F.; Villard, J.; Ferrari‐Lacraz, S.; Buhler, S.
Abstract : A total of 3 novel human leukocyte antigen‐B (HLA‐B) alleles were detected by next generation sequencing and confirmed by monoallelic sequencing.